2016
DOI: 10.1590/1809-9823.2016.14145
|View full text |Cite
|
Sign up to set email alerts
|

Collagen supplementation as a complementary therapy for the prevention and treatment of osteoporosis and osteoarthritis: a systematic review

Abstract: Introduction: Collagen hydrolysate is recognized as a safe nutraceutical, whose combination of amino acids stimulates the synthesis of collagen in the extracellular matrix of cartilage and other tissues. Objective: to conduct a systematic review of literature on the action of collagen hydrolysate in bone and cartilaginous tissue and its therapeutic use against osteoporosis and osteoarthritis. Method: a study of the PubMed, MEDLINE, LILACS, and SciELO databases was performed. Articles published in English and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 33 publications
0
25
0
6
Order By: Relevance
“…In addition to their structural function in cartilage and skin formation [ 1 , 2 ], as well as in the biomineralization of hard tissues [ 3 ] including bone [ 4 ] and dentine [ 5 ], collagens are involved in the regulation of diverse cellular functions and processes. During the last 60 years, research into collagens has evolved from the discovery of the structure of collagen [ 6 , 7 ], through studies on its chemistry and biochemistry [ 8 , 9 , 10 ], to present-day applications in cell therapy [ 11 ], biomedicine [ 12 , 13 , 14 ], cosmetics [ 15 ], and the food industry [ 16 ]. A rod-like triple-helical domain is the typical structural element in all collagens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their structural function in cartilage and skin formation [ 1 , 2 ], as well as in the biomineralization of hard tissues [ 3 ] including bone [ 4 ] and dentine [ 5 ], collagens are involved in the regulation of diverse cellular functions and processes. During the last 60 years, research into collagens has evolved from the discovery of the structure of collagen [ 6 , 7 ], through studies on its chemistry and biochemistry [ 8 , 9 , 10 ], to present-day applications in cell therapy [ 11 ], biomedicine [ 12 , 13 , 14 ], cosmetics [ 15 ], and the food industry [ 16 ]. A rod-like triple-helical domain is the typical structural element in all collagens.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen fibers confer tensile strength to these tissues. Hydrolyzed collagen is rich in amino acids such as glycine and proline, and after digestion it accumulates in the cartilage or skin and helps maintain stability or regeneration (7).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen may be one of such proteins. Promising randomized studies showed that the oral intake of 10 g of hydrolyzate of collagen per day within three months decreases pain and improves the function of joints in patients with diagnosed osteoarthritis and osteoporosis [11,12].…”
Section: за допомогою методів теоретичної кваліметрії проведено комплmentioning
confidence: 99%